Subsurface Identification Using Horizontal to Vertical Spectral Ratio and Inverse Velocity Modelling in Suoh Pull-apart Basin, Indonesia - Mulyasari, Rahmi; Sarkowi, Muh; Haerudin, Nandi; Utama, Hari Wiki; Widiatama, Angga Jati; Darmawan, I Gede Boy; Kurniawan, Andri; Husni, Yayan Mi’rojul; Hesti, Hesti; Fatmawati, Nofita; Marlina, Serli (Pandawa Institute, 2026)
Suoh is a pull-apart basin located along the Semangko segment of the Sumatra Fault Zone and filled by thick fluvio-volcanic and alluvial deposits that strongly amplify seismic waves and increase surface damage during earthquakes. This study aims to perform seismic micro-zonation of Suoh using the horizontal-to-vertical spectral ratio (HVSR) method combined with shallow shear-wave velocity (Vs) inversion to support hazard assessment and land-use planning in the Suoh aspiring geopark. Single station microtremor measurements were acquired at 30 sites and processed with Geopsy to obtain dominant frequency (f0), amplification factor (A0), and seismic vulnerability index (Kg). The HVSR curves were further inverted using the Dinver module to retrieve 1D Vs profiles, with initial models constrained by the global CRUST1.0 model and local geology. The results indicate strong lateral variability in site conditions, with low f0 and high A0 values concentrated in the central–western basin, producing high Kg and reflecting thick-soft sediments overlying deep engineering bedrock (Vs ≥ 800 m/s) at depths exceeding 80–100 m. These high-vulnerability zones spatially coincide with shallow seismicity associated with the Semangko Fault. Based on Kg, the study delineates low, moderate, and high seismic vulnerability zones, highlighting areas where seismic amplification and resonance effects are most pronounced. The combination of HVSR parameters with 2D Vs imaging provides a practical framework for identifying high-risk zones and guiding risk-informed land-use planning in tectono-volcanic basins such as Suoh.